2021
DOI: 10.3390/ijms22031374
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Immunoglobulin Gamma-3 Chain C Is a Promising Noninvasive Biomarker for Systemic Lupus Erythematosus

Abstract: We aimed to characterize the salivary protein components and identify biomarkers in patients with systemic lupus erythematosus (SLE). A proteomic analysis using two-dimensional gel electrophoresis and mass spectrometry was performed to determine the alterations of salivary proteins between patients with SLE and healthy controls, and the concentrations of the candidate proteins were measured through Western blot analysis and the enzyme-linked immunosorbent assay. The 10 differentially expressed protein spots we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Interestingly, proteomic analysis of saliva from patients with SLE identified the homodimer S100A8 to be almost four times higher as compared with controls. 44 It is noteworthy to mention that the differences found with regard to DA might reflect the close relationship between active LN and a high general DA score, since renal activity is highly weighted in the DA indices, especially in the SLEDAI-2K. 19 21 45 We found enhanced levels of the analysed markers in saliva in patients with high general DA, but not in patients with predominantly renal DA where urine was more informative.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Interestingly, proteomic analysis of saliva from patients with SLE identified the homodimer S100A8 to be almost four times higher as compared with controls. 44 It is noteworthy to mention that the differences found with regard to DA might reflect the close relationship between active LN and a high general DA score, since renal activity is highly weighted in the DA indices, especially in the SLEDAI-2K. 19 21 45 We found enhanced levels of the analysed markers in saliva in patients with high general DA, but not in patients with predominantly renal DA where urine was more informative.…”
Section: Discussionmentioning
confidence: 80%
“…Interestingly, proteomic analysis of saliva from patients with SLE identified the homodimer S100A8 to be almost four times higher as compared with controls. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Those data indicated that elevation of salivary lactoferrin is associated with lymphocytic infiltration on salivary glands and the immune imbalance that occurs in SS. However, salivary lactoferrin levels had been elevated in other conditions, such as periodontitis and SLE, suggesting a lack of specificity for biomarkers for SS [ 38 , 39 ].…”
Section: Salivary Biomarkers Of Sjogren’s Syndromementioning
confidence: 99%
“…Previously, we looked for the alteration of protein composition in saliva in patients with SLE to find a salivary biomarker for SLE and identified that several peptides including immunoglobulin gamma-3 chain C region (IGHG3) were elevated in the saliva of patients with SLE [ 4 ]. IGHG3 is immunoglobulin G (IgG)3, one of the subclasses of IgG.…”
Section: Introductionmentioning
confidence: 99%
“…However, the distribution of the IgG subclass in the sera and tissues and their respective functions have not been clearly elucidated in lupus. Previously, our data showed salivary IGHG3 levels were higher and associated with disease activity markers in patients with SLE [ 4 ].…”
Section: Introductionmentioning
confidence: 99%